Respuestas

2012-10-03T21:26:24+02:00

4^(x+1) - 2^(x+3) - 320 = 0

2^(2x+2) -2^(x+3) - 320 = 0

(2^x+1)^2 - 2.2.(2^x+1)-320=0     cambias de variable (2^x+1)=m


m^2-4.m-320=0

aspa simple,te quedaria así:


(m+16)(m-20)=0      igualas los 2 parentesis a cero

entonces:

m=-16

m=20                    reemplazas el m:          (2^x+1)=m

                                                                2^x+1=-16     Y            2^x+1=20

                                                             2.2^x=-16                     2.2^x=20

                                                                 2^x=-8                       2^x=10

                                                                x=log (-8)                      log2^x=log10

                                                                         2                          xlog2=1

                                                                                                  x=1/log2

                                                               

                                                                 



2012-10-03T21:47:57+02:00

4^(x+1) - 2^(x+3) - 320 = 0

2^(2x+2) -2^(x+3) - 320 = 0

(2^x+1)^2 - 2.2.(2^x+1)-320=0     cambias de variable (2^x+1)=m

 

m^2-4.m-320=0

aspa simple,te quedaria así:

 

(m+16)(m-20)=0      igualas los 2 parentesis a cero

entonces:

m=-16

m=20                    reemplazas el m:          (2^x+1)=m

                                                                2^x+1=-16     Y            2^x+1=20

                                                             2.2^x=-16                     2.2^x=20

                                                                 2^x=-8                       2^x=10

                                                                x=log (-8)                      log2^x=log10

                                                                         2                          xlog2=1

                                                                                                  x=1/log2